AFIKSASI BAHASA BALI: SEBUAH KAJIAN MORFOLOGI GENERATIF - Simpen, I Wayan (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 15 (2008): September 2008, 2008)
Abstract Studies on Balinese language, particularly on micro linguistics and macro linguistics, have been done both by domestic and foreign researchers. One of the studies that have been taken into account is morphology. After having reviewed the previous researches on morphology, it was found that the structural theory of morphology was mostly applied of which its linguistic phenomenon has not been satisfactorily considered. The derived words berbus ‘to get on bus’ and niyuk ‘to make use of knife’ have never been used. Meanwhile, medokaran ‘to get on two-wheel buggy’, mesepedaan ‘to bike’, numbeg ‘to dug up’ are usually used in Balinese. Based on this phenomenon, the generative morphology is therefore a relevant theory applied in the word formation process, particularly, Balinese affixation. The theory was first developed by Halle (1973), Aronoff (1976), Scalise (1984), and modified by Dardjowidjojo (1988). The basic principles of generative morphology are in terms of the word formation process that may result in the proper and natural forms, potential forms, and idiosyncratic forms. The word formation mechanism usually begins with idiosyncracy, filtering, and blocking. This theory also deals with ideal speakers that institutionally have got their innate languages. Therefore, this theory is able to linguistically explain such potential forms and idiosyncratic forms as niyuk ‘to make use of knife’, nyilet ‘to slice with a razor blade’, memotlot ‘to make use of pensil’.